CRM PRACTICES AND ITS EFFECTS ON PUBLIC AND PRIVATE SECTOR BANKS ACROSS CHENNAI - Manoj, Dr. G.; Jenefa, Dr. Leena (The journal of contemporary issues in business and government, 2022)
Banks have now become an indispensible part of economic growth. The relationship between a banker and a customer exists in the banking industry for a variety of reasons, including financial strain, the possibility of failure, inadequate marketing tactics, and others. Although few banks make an effort to adopt customer relationship management, many banks adhere to traditional marketing techniques (CRM). Long-term customer retention is the goal of CRM. In this paper, the researcher aims to analyze how consumers view banking services and find out how they feel about customer relationship management. A total of 175 respondents have provided the data, and samples have been chosen from Chennai's public and private sector banks. To learn what they think of Factor analysis has been used in CRM. The study concludes by trying to offer advice to banks on how to enhance customer relationship management in order to thrive in a cutthroat economy.